Investigating drug safety in pregnancy based on the German Pharmacoepidemiological Research Database (GePaRD): A proof‐of‐concept analysis on the association between valproate and spina bifida. Issue 2 (30th November 2022) - Haug, Ulrike; Kollhorst, Bianca; Schink, Tania; Thöne, Kathrin; Dathe, Katarina; Schaefer, Christof; Onken, Marlies
Abstract: Purpose: Large health‐care databases are increasingly used for research on drug utilization and safety in pregnancy. For the German Pharmacoepidemiological Research Database ( GePaRD ), covering ~20% of the German population, algorithms have been developed to identify pregnancies, to estimate their date of onset and to link mothers to their babies. Using this methodology, we aimed to conduct a proof‐of‐concept analysis on the known association between valproate (VPA) exposure in early pregnancy and spina bifida in the exposed child. Methods: We identified all pregnancies in GePaRD between 2006 and 2016 in women aged 12 to 50 years. To each VPA dispensation of these women, an exposure period was assigned, based on the dispensation date and the number of defined daily doses in the dispensed package. A pregnancy was classified as exposed to VPA in the critical time window if this exposure period overlapped with the first 55 days of pregnancy. Risk ratios were calculated for spina bifida in live births and induced abortions comparing VPA‐exposed ones to all pregnancies. Results: Overall, we identified 1 271 384 pregnancies fulfilling the inclusion criteria. Of these, 668 pregnancies (0.053%) were classified as exposed to VPA in the critical time window regarding spina bifida. An induced abortion accompanied by a diagnosis of spina bifida was observed in one of the VPA‐exposed pregnancies (0.15%) and in 154 of all pregnancies (0.012%), yielding a risk ratio of 12.4 (95% confidence interval [CI]: 1.7–88.2). Out of 775 875 pregnancies ending in a live birth, 366 (0.047%) were classified as VPA exposed. A diagnosis of spina bifida was coded in 3 of 366 VPA‐exposed live births (0.82%) and in 260 of all live births (0.03%), yielding a relative risk of 24.5 (95% CI: 7.9–76.0). Conclusions: Our proof‐of‐concept analysis based on GePaRD showed a strong association between intrauterine exposure to VPA and occurrence of spina bifida. The results are plausible and consistent with the literature, supporting the suitability of GePaRD and the developed algorithms to conduct studies on drug safety in pregnancy.